Entrepreneurial behaviour of lease land vegetable growers in Thiruvananthapuram district - Navitha Raj (Department of Agricultural Extension, College of Agriculture, 2018)
The present study entitled "Entrepreneurial behaviour of lease land vegetable growers in Thiruvananthapuram district" focused on the entrepreneurial behaviour, profile characteristics, nature and extent of lease land farming and the constraints faced by the lease land vegetable growers. The study comprised of eighty respondents who were selected randomly from four panchayats of Thiruvananthapuram district. Entrepreneurial behaviour of lease land growers with ten entrepreneurial attributes was the dependent variable. Twelve independent variables were selected based on judges’ rating. A structured interview schedule was used for data collection. Statistical tools such as arithmetic mean, standard deviation, frequency, correlation analysis and ANOVA were used for the analysis. Based on the analysis of data, it was found that majority (62.5%) of the farmers were having medium entrepreneurial behaviour. On comparison of four panchayats, it was found that there was no significant difference between the panchayats which means all the respondents of four panchayats had similar level of entrepreneurial behaviour. Distribution of respondents based on their entrepreneurial attributes was done using mean and standard deviation, it was found that majority (72.5%) of the respondents belonged to medium category of risk taking (72.5%), hope of success (61.25%), persuasibilty (61.25%), feedback usage (62.5%), self confidence (68.75%), knowledgeability (61.25%), persistence (60%), manageability innovativeness (60%) and achievement motivation (61.25%). (61.25%), In order to study the nature and extent of lease land farming, respondents were classified into different categories based on structure of tenancy, type of agreement, size of leased land, mode of rent, amount of rent paid and major vegetables under lease land cultivation. It was found that 66.25 per cent of respondents had informal and verbal contract followed by 25 per cent of them in the formal and written category. It might be due to the fact that owners are reluctant to go for formal/written agreement because of the fear of losing ownership of land since there is no government policy or procedure existing to protect their right over land. Majority (51.25%) of the respondents had leased an area of less than 1 acre. The probable reason might be because that the land owners fear that they might lose ownership of land and so are prepared to give only small stretch of land for lease. It was found that all the respondents paid their rent as cash. Over 67.5 per cent of the farmers paid their rent in the range Rs.18,640- Rs. 64,000 per acre per year. This variation in the rent amount was seen because of the difference in the pattern of lease land. Most of the farmers cultivated cucurbitaceous crops followed by cowpea. Majority (66.25%) of the respondents belonged to age category of more than 55 years. Majority (58.75%) of the farmers had an annual income of Rs. 50000- 100000. Majority of the respondents were in the medium category of problem solving ability (72.5%), market orientation (73.75%), information seeking behaviour (73.75%) and deferred gratification (73.75%). Three forth of the respondents had medium level of credit orientation and self reliance. Majority (66.25%) of the farmers used creative ideas to solve problems. With respect to environmental orientation and decision making, majority (56.25%) were in the medium category. The findings revealed that 50 per cent of the farmers were recycling their farm resources. Result of the correlation analysis between ten attributes of entrepreneurial behaviour and twelve independent variables revealed that four of the variables viz., problem solving ability, information seeking ability, creativity and decision making ability had positive and significant correlation with all (ten entrepreneurial attributes). With respect to overall entrepreneurial behaviour, problems solving ability, creativity, deferred gratification, market orientation, credit orientation and self reliance were found to have positive and significant correlation with entrepreneurial behaviour. Constraints faced by lease land farmers were found based on discussion with the respondents and ranking was done accordingly. High lease rent and owners demanding payment of rent before the cropping season got first rank among the lease land constraints. No fixed lease rent was the second most important constraint followed by lack of timely and sufficient credit facilities from banks, short tenure period, no voucher for payment of rent and lack of legal structure for agreement in the order. The major general constraints faced by farmers were instability in prices and lack of provision of vegetable crop insurance, high labour charges, inadequate extension service, lack of proper technical knowledge, failure of development departments to offer trainings to farmers, lack of proper marketing facilities, high cost of inputs and non availability of labour. Extension of land tenure to a period of three to four years, periodic evaluation by Krishibhavan officials, providing technical guidance by extension officials, timely availability of loans and insurance, provision of vegetable insurance based on the cost of cultivation of concerned crop were some of the suggestions given by respondents. Legalization of land leasing, creation of land bank, provide better extension agent support to adopt improved practices and technologies, timely and need specific training to farmers by developmental departments, improve marketing and transportation facilities without intermediaries, better availability of government subsidies and schemes, providing timely and sufficient credit facilities, promotion of value addition technologies were suggestions given by experts. Thus the study revealed that majority of the lease land vegetable growers belonged to the medium category of entrepreneurial behaviour. The constraints experienced by the farmers need the attention of government agency, policy makers, and extension organisation of the state for their redressal to boost up vegetable production.